(untitled) (Journal of actual problems of jurisprudence, 2018)
Article is devoted to research of a problem of qualification of investment contracts with participation of the state as legal forms (funds) of public-private partnership from a position of their contents. Formation of legal bases of implementation of public-private partnership requires inclusion of some provisions in investment and other legislation of Republic of Belarus. Then the investment contracts with participation of the state mediating state-private partnership in the infrastructure sphere will be able to regulate an order of creation (construction) of object of real estate, its operation, including for the purpose of rendering public (socially significant) services for satisfaction of public requirements that corresponds to the public-private partnership models which are successfully used in world practice. Key words: obsideri, imperium, lege contrahere, consortium.